Input Estimation for Extended-Release Formulations Exemplified with Exenatide - Trägårdh, Magnus; Chappell, Michael J.; Palm, Johan E.; Evans, Neil D.; Janzén, David L. I.; Gennemark, Peter (Frontiers in Bioengineering and Biotechnology, 2017)
Estimating the in vivo absorption profile of a drug is essential when developing extended-release medications. Such estimates can be obtained by measuring plasma concentrations over time, and inferring the absorption from a model of the drug's pharmacokinetics. Of particular interest is to predict the bioavailability - the fraction of the drug that is absorbed and enters the systemic circulation. This paper presents a framework for addressing this class of estimation problems, and gives advice on the choice of method. In parametric methods, a model is constructed for the absorption process, which can be difficult when the absorption has a complicated profile. Here, we place emphasis on nonparametric methods that avoid making strong assumptions about the absorption. A modern estimation method that can address very general input-estimation problems has previously been presented. In this method, the absorption profile is modeled as a stochastic process, which is estimated using Markov chain Monte Carlo techniques. The applicability of this method for extended-release formulation development is evaluated by analyzing a dataset of Bydureon, an injectable extended-release suspension formulation of exenatide, a GLP-1 receptor agonist for treating diabetes. This drug is known to have nonlinear pharmacokinetics. Its plasma concentration profile exhibits multiple peaks, something that can make parametric modeling challenging, but poses no major difficulties for nonparametric methods. The method is also validated on synthetic data, exploring the effects of sampling and noise on the accuracy of the estimates.